Selectivity Effects in Bimetallic Catalysis: Role of the Metal Sites in the Decomposition of Formic Acid into H2 and CO2 by the Coinage Metal Binuclear Complexes [dppmMM′(H)]+. Issue 7 (6th March 2017) - Zavras, Athanasios; Krstić, Marjan; Dugourd, Philippe; Bonačić‐Koutecký, Vlasta; O'Hair, Richard A. J.
Abstract: Design of new bimetallic catalysts requires an understanding of how cooperative effects of the metal sites influences reactivity. Here we show how switching one or both of the silver atoms in binuclear silver hydride cations, [dppmAg2 (H)] + (dppm=1, 1‐Bis(diphenylphosphino)‐methane), with all combinations of copper and/or gold maintains selective dehydrogenation of formic acid, enhancing reactivity by up to 2 orders of magnitude. This is a key step in the selective, catalyzed extrusion of carbon dioxide from formic acid, HO2 CH, with important applications in hydrogen storage and in situ generation of H2 . Decarboxylation of [dppmMM′(O2 CH)] + through collision induced dissociation regenerates [dppmMM′(H)] + . DFT calculations provide insights into these cooperative effects. The copper homobinuclear catalyst performs best overall. Abstract : Break Free ! Bimetallic coinage metal hydrides react with formic acid to liberate hydrogen. By systematically changing the metal centres reactivity trends have been established. The reaction efficiency can be increased by up to 2 orders of magnitude.